Philosophical Foundations of Transformation in the Information Space in the New Uzbekistan - Rasulov Azizkhan Mukhamadgadirovich (Penerbit Jurnal Indonesia, 2024)
The article analyzes the philosophical foundations of information space transformation. The solution to the general philosophical problem of information as an attribute of matter in the modern world is researched. Also, this issue, in turn, is the subject of debates between attributive and functional approaches, supporters of the functional approach associate the phenomenon of information with the existence of the subject of knowledge, rejecting its functionality at the level of inorganic systems. The conclusions of the supporters of the attributive approach that information is a general characteristic, an attribute of organic and inorganic natural matter, are stated.